Facebook addiction among female university students. - S. Z., Sharifah Sofiah; Omar, Siti Zobidah; Bolong, Jusang; Osman, Mohd Nizam (Vasile Goldis Western University, 2011)
Facebook is used widely by the students in fulfilling their basic needs and interaction. It was becoming a popular medium for socializing online and tools to facilitate friendship. Female students used Facebook for different kind of motives from social interaction to communication. The frequent use of Facebook brought an addiction toward the site and simultaneously influent students’ daily life at large. The phenomenon of Facebook addiction in Malaysia is rising among university students especially female. The objective of this study is to identify the relationship between female students’ motives for Facebook use and Facebook addiction. The five motives identified were social interaction, passing time, entertainment, companionship, and communication. This study involved 380 female students (Facebook users) from Universiti Kebangsaan Malaysia and Universiti Tenaga Nasional. Findings of the study showed that there are significant relationship between female students’ motives for Facebook use and Facebook addiction. As a conclusion, social interaction, passing time, entertainment, companionship and communication motives were among the major contributor to the addiction of Facebook site. It is hoped that the results of the study will be applicable to service providers, current users, and potential users of Facebook. This study recommends that motives for Facebook use is one of the factors contributing to Facebook addiction among students.